Pengaruh Kompetensi, Akuntabilitas dan Independensi Terhadap Kualitas Audit dengan Etika Auditor Sebagai Variabel Moderating - Shelly Amelia Sari; Emilia Gustini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes the influence of competence, accountability, and independence on audit quality, with auditor ethics as a moderating variable. Using a quantitative approach and SmartPLS 4 analysis, data was collected through a questionnaire distributed to 45 auditors at PT. Perkebunan Nusantara I Regional VII Kebun Beringin. The research results indicate that competence, accountability, and independence directly have a positive and significant effect on audit quality. The moderating analysis further reveals that auditor ethics significantly strengthens the relationship between competence and audit quality, as well as between accountability and audit quality. However, auditor ethics does not have a significant role in strengthening the relationship between independence and audit quality. This finding concludes that auditor ethics is an important factor that can enhance the effectiveness of auditor competence and accountability in producing high-quality audits.